Winter seaducks in the Moray and Dornoch Firths, Scotland - Mudge, Greg P; Allen, Dave S (Wildfowl, 1980)
The numbers, distribution and behaviour of seaducks in the Moray and Dornoch Firths are described for the winters of 1977-1978 and 1978-1979. This area is at present the major seaduck wintering site in Great Britain, with an average of about 20,000 birds. It holds internationally important concentrations of Common Scoter Melanitta nigra, Velvet Scoter M. fusca, Long-tailed Duck Clangula hyemalis and Red-breasted Merganser Mergus serrator, and nationally important concentrations of Eider Somateria mollissima, and Goldeneye Bucephala clangula. The majority of the ducks occurred at five sites Spey Bay, Burghead Bay, Culbin and Nairn Bars, Cromarty Rosemarkie Nairn, and the northern outer Dornoch Firth. In both winters Spey Bay was of overwhelming importance. However, the relative use of individual sites varies considerably from year to year.